2010
DOI: 10.1128/jb.00143-10
|View full text |Cite
|
Sign up to set email alerts
|

The Virulence of aDickeya dadantii3937 Mutant Devoid of Osmoregulated Periplasmic Glucans Is Restored by Inactivation of the RcsCD-RcsB Phosphorelay

Abstract: Dickeya dadantii is a pectinolytic phytopathogen enterobacterium that causes soft rot disease on a wide range of plant species. The virulence of D. dadantii involves several factors, including the osmoregulated periplasmic glucans (OPGs) that are general constituents of the envelope of proteobacteria. In addition to the loss of virulence, opg-negative mutants display a pleiotropic phenotype, including decreased motility and increased exopolysaccharide synthesis. A nitrosoguanidine-induced mutagenesis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 40 publications
(55 reference statements)
0
48
0
Order By: Relevance
“…By contrast, the other known suppressors of the Opg phenotype, i.e. the rcsC gene (Bouchart et al, 2010), the kdgR and the pecT genes (this study), allowed restoration only on potato tubers. All these suppressors restore pectinase synthesis and secretion, and the data presented here show that this restoration is sufficient to restore virulence in potato tubers in strains devoid of OPGs.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…By contrast, the other known suppressors of the Opg phenotype, i.e. the rcsC gene (Bouchart et al, 2010), the kdgR and the pecT genes (this study), allowed restoration only on potato tubers. All these suppressors restore pectinase synthesis and secretion, and the data presented here show that this restoration is sufficient to restore virulence in potato tubers in strains devoid of OPGs.…”
Section: Discussionmentioning
confidence: 72%
“…The role of OPGs remains unclear and is probably indirect. In a previous study, the relationship between OPGs and the phosphorelay RcsCDB was demonstrated (Bouchart et al, 2010). Direct interaction between the RcsC and/or RcsD sensor proteins and OPGs cannot be excluded, as the periplasmic domain of both proteins may interact with these periplasmic glucans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we showed that the three main repressors of virulence of D. dadantii (namely: KdgR, PecT and PecS) cannot be derepressed in opg deficient mutant strains (BontempsGallo et al, 2014). Loss of OPGs affects the perception of the environment of bacteria in such a way that bacteria were unable to recognize the environment properly, including its various plant hosts (Bouchart et al, 2010;Bontemps-Gallo et al, 2013, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In these strains, the secondary mutation encoded a mutated RcsC2 sensor with an increased phosphatase activity, no RcsC sensor or a non-phosphorylatable RcsB D56N regulator, respectively (Bouchart et al, 2010;Bontemps-Gallo et al, 2013). Phosphorylation of the RcsB D56N protein is impossible since its phosphorylatable aspartic acid residue at position 56 was changed to an asparagine residue.…”
Section: Introductionmentioning
confidence: 99%